Yam improvement for income and food security in West Africa - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The project will adopt a value chain approach and will build the capacity of farmers and farmers’ organizations (FOs) and their service providers (SPs) (e.g. NARES, NGOs, input suppliers, etc.) to ensure that technical innovations as well as improved access to yam markets will sustainably benefit smallholder yam producers. It will ensure that not only significant numbers of beneficiaries are reached, but it will provide the opportunity for future sustainability and scalability. Gender and diversity analyses will be built into value chain and scoping studies to ensure that project activities are designed to specifically benefit women and small-scale farmers groups.